MANAJEMEN STRATEGIS PENDIDIKAN PESANTREN MUADALAH MUALLIMIN DALAM MENINGKATKAN MUTU PEMBELAJARAN SANTRI - Acep Nurulah; Muammar Zulfiqri (Universitas Islam Depok, 2024)
This study reveals that teacher management is a profession with limited professional skills, and teacher organizations do not implement effective strategies. Research focuses on strategic management of teacher education, including analyzing the school environment, formulating strategies, implementing strategies, evaluating strategies, and solving problems. This research uses qualitative methods which include observation and documentation, and uses theories such as the Grand theory of strategic management, learning theory, and student concepts. The study also used triangulation to validate the data. Research findings include analyzing the school environment using SWOT analysis, formulating strategies, implementing strategies, evaluating strategies and overcoming problems. Research concludes that teacher management is a profession with limited professional skills and is not effective in improving student learning.